Understanding Gujarat pols - 2019 - Manish and Singh, Vijendra (Social Science in Perspective)
This paper explains 2019 Lok Sabha verdict in Gujarat in the backdrop of last parliamentary and state assembly elections. It argues that after its best performance in 2014 parliamentary election in the state. BJP faced serious debacle in 2017 state assembly election. As a consequence, it re calibrated its strategy and adopted multi pronged strategy during 2019. In 2019, BJP won many of the lost communities and castes, a and improved its during performance across the regions. Also. BJP$1 (Bs narrative during election campaign was much more targeted and the electorate than that of the opposition. The paper also argues that BJP$1 (Bs resounding victory in 2019 was also become of voters making distinction between the state and the national elections with Narendra Modi as the Prime ministerial candidate. - Reproduceds
Keywords: Elections - Gujarat